Phylogenetic analysis of the Euschistus group (Hemiptera: Pentatomidae) suggests polyphyly of Dichelops Spinola, 1837 with the erection of Diceraeus Dallas, 1851, stat. rev. Issue 4 (28th July 2020) - Barão, Kim R; Ferrari, Augusto; Grazia, Jocelia
Abstract: Carpocorini are the most diverse tribe within Pentatominae, comprising about 100 genera and 500 species, with the highest diversity found in the Neotropics. Within Carpocorini, some groups of genera have been, formally or informally, proposed based on morphological similarities and taxonomic history. The Euschistus group was informally proposed and comprises 20 genera, including Euschistus Dallas, 1851 and Dichelops Spinola, 1837. Both of these genera had their monophyly under dispute recently. Dichelops, which includes the species commonly known as the green‐belly stink bug, comprises 16 species in three subgenera, with an exclusively Neotropical distribution. The genus was revised recently, and for each subgenus, a set of distinct morphological characters was listed, which allow their precise identification. We tested the monophyly of the Euschistus group and of Dichelops under parsimony criteria using discrete and continuous characters and two‐character weighting methods. The Euschistus group was paraphyletic, and Dichelops was polyphyletic in every analysis, and the taxonomic characters formerly proposed as diagnostic for the genus and its subgenera were homoplastic. On the basis of the phylogenetic result, we propose the erection of Diceraeus Dallas, 1851, stat. rev. to the status of genus and Dichelops comprising two subgenera, the nominal and Prodichelops Grazia, 1978. This decision has implications for applied entomology, because species of Diceraeus are important crop pests in the Neotropics.